2020
DOI: 10.1590/1808-1657000092020
|View full text |Cite
|
Sign up to set email alerts
|

Causes of equine abortion, stillbirth, and perinatal mortality in Brazil

Abstract: Abortion and complications in reproduction are important causes of economic loss in horse breeding. Studies of its causal agents can help to identify the primary pathogens or other factors involved and define appropriate measures to reduce its occurrence. This research aimed to investigate the primary causes of equine abortion, stillbirth, and perinatal mortality in regions of Brazil. Tissue from aborted fetuses, stillbirths, neonates and foals submitted to the Biological Institute of São Paulo, Brazil, from J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 19 publications
1
9
0
Order By: Relevance
“…All cases had lesions consistent with EHV-1 infection and the presence of EHV-1 was confirmed by PCR and IHC. EHV-1 is a well-known cause of abortion in mares ( 4 13 ). Viral DNA was also found in three abortion cases, which all had lesions consistent with fetal death due to UCT and lacked EHV-1 pathology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All cases had lesions consistent with EHV-1 infection and the presence of EHV-1 was confirmed by PCR and IHC. EHV-1 is a well-known cause of abortion in mares ( 4 13 ). Viral DNA was also found in three abortion cases, which all had lesions consistent with fetal death due to UCT and lacked EHV-1 pathology.…”
Section: Discussionmentioning
confidence: 99%
“…Diagnostic studies of aborted, premature, and stillborn foals have revealed a wide range of causes (4)(5)(6)(7)(8)(9)(10)(11)(12)(13). However, the results of these studies cannot be directly compared, since different study designs, methods, and diagnostic criteria, were used by different researchers.…”
Section: Introductionmentioning
confidence: 99%
“…The aforementioned low abortion rate of EHV-1 (1. 09%) was in concurrences with Silva et al (2020) who recorded [2/105, (1. 9%)] of equine abortions in Brazil caused by EHV1 infection.…”
Section: Discussionmentioning
confidence: 61%
“…Escherichia coli is a largely commensal bacteria in the gastrointestinal tracts of mammals, but it has been reported to be a causal agent in some nosocomial infections (Sato et al, 2020), and as a cause of abortion in mares (Silva et al, 2020).…”
Section: Discussionmentioning
confidence: 99%